Does training improve the usability of online Extension tools? - Agee, Alyssa; Johnson, Wendy (My University, 2017)
Times are changing; however, our current state of extension information delivery has not yet evolved to match user need. For example, Kansas farmers can sometimes only find crop management information on the KSU website as downloadable PDFs, or mailed paper booklets. Some of the past attempts at online extension delivery, such as the eXtension program, have not succeeded in adoption by target audiences (1). Several studies found that ease-of-use and awareness of eXtension hampered its adoption (2,3). We will use the lessons learned from the eXtension project for developing and promoting a new online program, a customizable extension experience, myFields.info.